Fresno City Council Swearing In Karen Humphrey Mayor and Council Members - Watkins, Howard::::::::: (1989)
? and Mayor Karen Humphrey embracing each other with City of Resolution facing audience Shows resolution signed by the members of the Los Angeles City Council